Arah dan Tujuan Pendidikan Islam - Alimatusakdia Panggabean; Ahmad Fachrizal; Azizah Hanum (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
In order for Islamic education to be used to address issues that affect people at all levels from young children to adults it is necessary to identify the direction of the discipline in a comprehensive manner. In order to find facts and the outcomes of someone's thoughts, this research employs a library technique with a descriptive analysis strategy, which entails searching, analyzing, creating interpretations, and generalizing the findings of research from primary and secondary sources. According to this study, the purpose of Islamic education is to develop worship specialists, develop a pious personality, and produce the Khalifah of Allah on Earth. in an effort to foster the uniqueness of children. Comprehensive explanations of this are provided in Islam. Children's rights and efforts to safeguard them are in fact upheld and appreciated. a quality, moral, intellectual, and spiritual generation is being prepared entirely from the outside. The preparation of people to believe in and serve Allah is the ultimate purpose of Islamic religious education. Goals are criteria of performance that can be identified, which help to focus efforts on a plan and serve as a springboard for accomplishing further goals. Additionally, the objective is to reduce the path space to choose a point so that we can concentrate on the objective.